2020
DOI: 10.32794/mr11250057
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin inhibits human melanoma cells proliferation and invasion via cell cycle arrest and cytoskeleton remodeling

Abstract: Among skin cancers, melanoma has the highest mortality rate. The heterogeneous genetic melanoma background leads to a tumor-propagating capacity particularly important in maintaining therapeutic resistance, and tumor recurrence. The identification of efficient molecules able to control melanoma progress represents an important opportunity for new therapeutic strategies, particularly in combination with the current standard-of-care treatments. In this context, several s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…It possesses various functions ranging from regulating circadian rhythms to antioxidant, anti-inflammatory, immunomodulatory, and anti-aging properties. Importantly, it also exerts cytoprotective effects in normal cells and triggers apoptotic signals in oncogenic cells [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. As melatonin is lipophilic in nature, it can easily penetrate through the cellular membrane to protect intracellular structures such as DNA and mitochondria from oxidative stress induced by free radical generation.…”
Section: Melatonin As Drug Repurposingmentioning
confidence: 99%
See 1 more Smart Citation
“…It possesses various functions ranging from regulating circadian rhythms to antioxidant, anti-inflammatory, immunomodulatory, and anti-aging properties. Importantly, it also exerts cytoprotective effects in normal cells and triggers apoptotic signals in oncogenic cells [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. As melatonin is lipophilic in nature, it can easily penetrate through the cellular membrane to protect intracellular structures such as DNA and mitochondria from oxidative stress induced by free radical generation.…”
Section: Melatonin As Drug Repurposingmentioning
confidence: 99%
“…Melatonin also activates the apoptosis-targeting proteins p53 and p21. [ 33 , 34 , 35 , 38 , 45 ]. Apart from causing apoptosis, melatonin and its metabolites act as antioxidants forming a free radical scavenger cascade protecting tissues from oxidative damage.…”
Section: Melatonin As Drug Repurposingmentioning
confidence: 99%
“…It is not surprising that the migration of metastatic melanoma, which is dependent on acidic pH e , is promoted by the prion protein [ 67 , 484 , 485 ]. Experimental studies on skin reconstructed with melanoma cell lines found treatment with 1 mM melatonin controlled growth and impaired invasion and metastasis by disrupting cytoskeleton formation [ 486 ] while high-dose melatonin (5 mg/m 2 /day to 700 mg/m 2 /day) showed stable, favorable responses in human subjects diagnosed with advanced malignant melanoma [ 487 ]. Melatonin also prevented the aggressive phenotype shifts in breast cancer cell lines maintained under acidosis conditions by modulating proliferation and apoptosis [ 488 ].…”
Section: Melatonin May Promote Prp Physiological Functions and Inhibi...mentioning
confidence: 99%
“…The molecular mechanisms by which melatonin enhances TNT formation and functionality remain unknown and deserve intensive study. A modulatory effect of melatonin on the cytoskeleton has been reported in different types of cells [102][103][104] and cytoskeletal rearrangements seem to protect the neuro-cytoskeleton from damage caused by free radicals, which, in turn, contributes to cell survival.…”
Section: Melatonin: a Possible New Role In Mscs Communication?mentioning
confidence: 99%